What's become of cultural studies? - Turner, Graeme (Sage, 2012)
"This original, sharp and engaging book draws the reader into a compelling exploration of cultural studies in the twenty-first century. It offers a level-headed account of where cultural studies has come from, the methodological and theoretical dilemmas that it faces today and an agenda for its future development. In an age in which the relevance of cultural studies has been called into question, this book seeks to generate debate. Focusing upon the actual practice of cultural studies within the university today, it asks whether or not cultural studies has really managed to maintain a connection with its original political and ethical mission and comments on the strategies needed to regain the initiative."Provided by goodreads.com.